Use of Anesthesia for Imaging Studies and Interventional Procedures in Children. Issue 4 (October 2016) - Huang, Yolanda Y.; Li, Lucy; Monteleone, Matthew; Ferrari, Lynne; States, Lisa J.; Riviello, James J.; Kernie, Steven G.; Mencin, Ali A.; Gupta, Sumit; Sun, Lena S.
Abstract : Ongoing investigation from the Pediatric Anesthesia NeuroDevelopment Assessment (PANDA) study hopes to examine the long-term effect on cognitive and language development of a single anesthetic exposure in children undergoing inguinal hernia repair. The fifth PANDA Symposium, held in April 2016, continued the mission of previous symposia to examine evidence from basic science and clinical studies on potential neurotoxic effects of anesthetics on developing brain. At the 2016 Symposium, a panel of specialists from nonsurgical pediatric disciplines including anesthesiology, radiology, neurology, gastroenterology, oncology, cardiology, and critical care reviewed use of anesthesia in their practices, including how concern over possible neurodevelopmental effects of early childhood anesthetic exposure has changed discussion with patients and families regarding risks and benefits of imaging studies and interventional procedures involving sedation or anesthesia. This paper summarizes presentations from nonsurgical pediatric specialists at the 2016 PANDA Symposium.